Working women in the sandwich generation : theories, tools and recommendations for supporting women's working lives /: theories, tools and recommendations for supporting women's working lives. (2022) - Rajahonka, Mervi; Kwiatkowska-Ciotucha, Dorota; Timmers, Miet; Załuska, Urszula; Villman, Kaija; Lengeler, Veerle; Gielens, Tim
No abstract available